Attitude and Perception of Undergraduate Medical and Dental Students towards Problem-Based Learning in Karachi - Syeda Saima Qamar Naqvi, Mahrukh, Yasmeen Fatima Zaidi, Badar Akram, Gulmina Saeed Orakzai, Aliya Islam, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The goal of this study is to assess students' attitudes and perceptions of problem-based learning sessions. Methods: A cross-sectional survey study was conducted at Medical College of Karachi from February to May 2022 with preclinical medical and dental students. Students' attitudes towards and perceptions of problem-based learning sessions were examined using an electronic questionnaire.. SPSS 21 was used to analyze the data. Results: Overall, the students had a positive attitude towards all of the items, including self-directed learning, critical thinking, integrating basic concepts into clinical science, identifying knowledge gaps, and improved problem-solving skills. Despite the fact that PBL took a lot of time, the majority of students found PBL interesting. Conclusion: Most of the preclinical students favored PBL and believe it should be included in the curriculum alongside other teaching methods. Keywords: Problem-based learning (PBL), Medical students, Dental students, Perception, Attitude